THE ROLE OF IDENTITY IN THE KOREA REUNIFICATION PROCESS: AN ANALYSIS - Utomo, Ario (UNIDA Gontor, 2020)
This article attempts to understand the source of the reunification process in the Korean Peninsula. This is descriptive qualitative research using secondary data and utilises constructivism approach that offers norms and identity as the source of international relations. In addition, this article also using realism theory since the two countries often using hard strategies. In this preliminary studies found that the failure of Korean reunification is due to the difference of interest combined with the complexity of political identity between the two countries. Therefore, this is an important topic to examine at least to understand the construction of identity during the reunification process.